A non-vacuum dip coated SiO2 interface layer for fabricating CIGS solar cells on stainless steel foil substrates. (15th January 2021) - Misra, Prashant; Atchuta, S.R.; Mandati, Sreekanth; Sarada, B.V.; Rao, T.N.; Sakthivel, S.
Highlights: CIGS solar cells are made on commercial SS foils by using a SiO2 interface layer (IL). 1 μm thick SiO2 layer is deposited on SS foil by a solution-based dip coating method. SiO2 IL improves mechanical stability and grain structure of Mo and CIGS absorber. Solution-based IL could be an economical option for making CIGS panels on SS foils. Abstract: A novel solution processed SiO2 coating is investigated for use as an interface layer between the substrate and Mo back contact for making CIGS solar cells on flexible SS foils. Prior to deposition of Mo, a ~ 1 μm thick SiO2 layer is applied on commercially available SS foils using an economical non-vacuum dip coating method. CIGS absorbers as well as complete CIGS solar cells having the structure Mo/CIGS/CdS/i-ZnO/AZO are grown on SS foils with and without the interface layer and their characteristics are compared. The interface layer improves the adhesion and high temperature mechanical stability of Mo back contact. Although phase formation of CIGS absorber is not influenced by the presence of interface layer, the grain structure and surface morphology are positively impacted, resulting in an enhanced solar cell performance. Composition measurements did not reveal any increase of Fe content in the CIGS absorber after the high temperature selenization step. However, the role of interface layer in blocking the diffusion of Fe from the SS substrate is uncertain, as the high-quality Mo back contact itself could be acting as an efficient Fe barrier layer. The interface layer is capable of electrically isolating Mo back contact from the underlying SS substrate, thus offering the prospect of monolithic integration for making lightweight CIGS modules. With a simple and inexpensive deposition process, which can be easily upscaled for large substrates, the dip-coated SiO2 interface layer could be a suitable alternative for various existing vacuum deposited layers in realizing low-cost flexible CIGS modules.